A prefabricated civil defense structure - Azizov, Taliat N.; Lyulchenko, Vyacheslav H.; Orlova, Olga M. (Kyiv National University of Construction and Architecture, 2024)
To date, there remains a high level of danger of being hit by various types of missiles to the population of Ukraine. Given the requirements of Article 20 of the Civil Protection Code of Ukraine, the obligation of business entities of all forms of ownership to provide their employees with collective protection means is established. According to Article 32 of the Code, in case of putting the unified state civil protection system and its components on high alert, civil protection structures, dual-purpose structures, and simple shelters, regardless of ownership, must be put in place to receive the public within a period not exceeding twenty-four hours. The problem of rapid sheltering of the population can be solved through the use of prefabricated protective structures that will be small in size and can be quickly constructed without the use of heavy machinery. The purpose of the study is to develop proposals for the construction of a small-sized civil defense structure that can be built quickly and without the use of heavy machinery, as well as a methodology for calculating the joints of the proposed structure. The most effective basic ways and means of protecting the population are the use of civil defense structures, but due to lack of funds and control over their maintenance, the protective structures do not meet the established standards. Inspections by state commissions have shown that most of the shelters, anti-radiation, simple and dual-purpose shelters are flooded, the power, water and sewage systems are disconnected, ventilation systems are broken, furniture is missing, etc. And some are used for other purposes. According to Chapter 7 of the Civil Code of Ukraine, civil defense structures include various types of structures, including prefabricated protective structures. Existing risks and threats make it more relevant to install prefabricated civil defense structures that are built (manufactured, assembled) in a short time from special structures (products). The problem of inventing a prefabricated protective structure for the population that does not require the use of machinery for installation and can be quickly constructed by one team of builders remains a priority area of research. The paper proposes a design of prefabricated elements that can be assembled by hand, and shows a method for calculating the strength of the dressing seams that connect the prefabricated elements. Despite its simplicity, the structure is highly durable and does not require any additional reinforcements, which is a significant advantage over brick structures.